Distance teaching of probability theory and statistics - Bikulčienė, Liepa; Dabulytė, Jurgita (Lietuvos matematikos rinkinys, 2003)
In these latter years the interest of remote teaching is booming. In foreign countries such teaching method is widely used. A lot of Lithuanian universities are also interested to prepare good distance models, which can complete with foreign modules and makes easier to work with our students. In this work the distance module ``  ` Probability theory and statistics'' is presented. The second year extramural students of Kaunas technology university took part in this analysis. The main goal of this work is to find out lacks and advantages of such teaching method.